2022
DOI: 10.1177/03635465221087365
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Magnetic Resonance Imaging Outcomes After Microfracture Treatment With and Without Augmentation for Focal Chondral Lesions in the Knee: A Systematic Review and Meta-analysis

Abstract: Background: Focal cartilage lesions represent a common source of knee pain and disability, with the potential for the development and progression of osteoarthritis. Currently, microfracture (MFx) represents the most utilized first–line surgical treatment for small, focal chondral lesions. Recent investigations have examined methods of overcoming the limitations of MFx utilizing various augmentation techniques. Purpose: To perform a systematic review and meta–analysis evaluating clinical and radiographic outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Fibrocartilage-like tissue did regrow at the defect area in various studies. 5,6 Similarly, our result of HE staining showed that fibrochondrocytes were concentrated at the part close to the acetabulum while the periphery formed a matrix of fibroblast cells and fibrochondrocytes within the regrown tissue at 6 weeks. The technique of bone marrow stimulation did have the capacity to re-create fibrocartilage-like tissue at the labral defect area through differentiation of the mesenchymal stem cells induced by the surrounding environment.…”
Section: Discussionsupporting
confidence: 52%
“…Fibrocartilage-like tissue did regrow at the defect area in various studies. 5,6 Similarly, our result of HE staining showed that fibrochondrocytes were concentrated at the part close to the acetabulum while the periphery formed a matrix of fibroblast cells and fibrochondrocytes within the regrown tissue at 6 weeks. The technique of bone marrow stimulation did have the capacity to re-create fibrocartilage-like tissue at the labral defect area through differentiation of the mesenchymal stem cells induced by the surrounding environment.…”
Section: Discussionsupporting
confidence: 52%
“…Microfracture with augmentation resulted in greater improvement by a clinically important margin in Lysholm and MOCART (magnetic resonance observation of cartilage repair tissue) scores; however, there were no differences in the mean improvement in the visual analog scale (VAS) pain, IKDC, or Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores. A subgroup analysis in which cases with concomitant high tibial osteotomy were excluded demonstrated the same clinical findings 13 .…”
Section: Kneementioning
confidence: 77%
“…A focal chondral defect within the knee remains a challenging problem with many surgical treatment options. Fortier et al 13 completed a systematic review and meta-analysis comparing microfracture treatment with and without augmentation for focal chondral defects in the knee, including 14 studies of 744 patients with a mean age of 46.8 years, a mean follow-up of 26.7 months, and a mean chondral lesion size ranging from 1.3 to 4.8 cm 2 . Microfracture augmentation with orthobiologics (platelet-rich plasma, hyaluronic acid, mesenchymal stem cells) was used in 57% of studies and scaffolds (biomembranes, fibrin-based) were used in 43% of studies.…”
Section: Kneementioning
confidence: 99%
“…However, a subjective synthesis performed with 4 randomized controlled trials noted that 2 trials showed significantly greater improvements in the KOOS or IKDC score after combined microfracture and augmentation at the 2-year follow-up; conversely, the other 2 studies showed no differences when compared with microfracture alone. Recently, Fortier et al 11 performed a systematic review and meta-analysis of 744 patients within 14 studies comparing augmented microfracture using various types of adjuvants and isolated microfracture. They reported a significant improvement in the Lysholm score for patients who underwent augmented microfracture, but similar improvement in VAS, IKDC, or Western Ontario and McMaster Universities Arthritis Index (WOMAC) scores compared with patients who underwent only microfracture.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of randomized controlled trials comparing the outcomes after microfracture treatment with and without augmentation reported significant improvements in the postoperative MOCART score after microfracture with augmentation (mean, 64.3) as compared with that after isolated microfracture (mean, 46.1). 11 However, this meta-analysis included only 3 studies owing to a lack of high-quality randomized controlled comparison studies, of which 2 used porcine-derived collagen as an augment. Our study adds further evidence that augmentation with microfracture could improve the quality of the repaired cartilage, as compared with isolated microfracture.…”
Section: Discussionmentioning
confidence: 99%